In vitro study of cypermethrin on human spermatozoa and the possible protective role of vitamins C and E. (16th December 2013) - Zalata, A.; Elhanbly, S.; Abdalla, H.; Serria, M. S.; Aziz, A.; El‐Dakrooy, S. A.; El‐Bakary, A. A.; Mostafa, T.
Summary Cypermethrin, a type II synthetic pyrethroid pesticide, is widely used in pest control programmes in agriculture and public health. This study aimed to assess the potential effect of cypermethrin on human spermatozoa and the possible ameliorative effects of vitamins C and E. Semen samples of 20 healthy normozoospermic men were divided into six aliquots at room temperature. The first aliquot served as control not exposed to treatments, and the second was incubated with 20 mm vit. C and 2 mm vit. E where the third one was exposed to 10 μm cypermethrin for 6 h. The other three aliquots were incubated with vit. C, vit. E and both vitamins for 30 min before cypermethrin exposure. Semen aliquots were analysed for sperm motility, sperm viability, hypo‐osmotic swelling test and modified alkaline comet assay. The results demonstrated a significant decrease in sperm motion, sperm function and increased sperm DNA damage in the cypermethrin group. Addition of vitamins C and E alone/combined led to significant improvement in sperm motion, sperm function and DNA damage, being maximal with both vitamins together. It is concluded that in vitro cypermethrin can alter sperm function and induce DNA damage in spermatozoa, which is improved after using vitamins C and E.